Mammalian Fauna of Dharamshala and its Suburbs of District Kangra, Himachal Pradesh, India - Thakur, Savita; Banyal, H.S. (Asian Journal of Biological and Life Sciences)
Dharamshala is a hill area which lies at the feet of the Dhauladhar range. Studies on the mammalian fauna of Dharamshala and its suburbs of District Kangra, Himachal Pradesh, were carried out during different seasons of the years from 2012-2020. After the selection of the study area, the investigations regarding the present study were done by using direct and indirect methods. The direct methods include the visual sighting of the animal species, whereas the indirect methods include footprint and faecal matter study of the animals. The present study showed the presence of 23 species of fauna belonging to 23 different genera, 17 families and seven orders. A maximum of 8 species have an association with Order Carnivora, followed by order Artiodactyla with five species, Rodentia with four species and Primate and Lagomorpha with two species of each of the order. Insectivora and Chiroptera with single species from each order were observed in the Dharamshala region. It has been observed that the maximum no. of mammalian species i.e. 17 species in Dharamshala and its suburbs, are placed under Least Concern by International Union for Conservation of Nature (IUCN, 2013) whereas one species has been categorized as endangered, two species are vulnerable, and three species have been declared threatened by IUCN.
Keywords: Dharamshala; Himachal Pradesh; Kangra; Mammalian fauna